Morphological and molecular evidence reveals a new species of Anteaeolidiella (Mollusca, Nudibranchia, Aeolidiidae) from the Yellow Sea, China - Zhang, Shuqian; Zhang, Suping (Zootaxa, 2023)
During an investigation of nudibranch gastropods in the Yellow Sea, several specimens were collected from the intertidal zone of Qingdao, Shandong Province, China. Morphological observation of their external and internal anatomy revealed that they represent an undescribed species belonging to the genus Anteaeolidiella M. C. Miller, 2001. This new species, Anteaeolidiella decorus sp. nov., can be differentiated from other congeners by both external morphology and internal anatomy. Phylogenetic analyses of two mitochondrial (COI, 16S rRNA) and a nuclear (H3) gene using Bayesian inference, maximum likelihood analysis, and species delimitation analyses also support the separation of Anteaeolidiella decorus sp. nov. from its congeners.